2015
DOI: 10.7146/lom.v8i14.22057
|View full text |Cite
|
Sign up to set email alerts
|

Tema 2: The NAO robot as a Persuasive Educational and Entertainment Robot (PEER) – a case study on children’s articulation, categorization and interaction with a social robot for learning

Abstract: The application of social robots as motivational tools and companions in education is increasingly being explored from a theoretical and practical point of view. In this paper, we examine the social robot NAO as a Persuasive Educational and Entertainment Robot (PEER) and present findings from a case study on the use of NAO to support learning environments in Danish primary schools.In the case study we focus on the children’s practice of articulation and embodied interaction with NAO and investigate the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The 25 degrees of freedom (Figure 1) provide NAO the capability to mimic almost all humanlike movement. Due to such features, NAO can be used in a multitude of the research environment, including assistive robotics, 42,47 healthcare robotics, [34][35][36] educations robotics, 48,49 etc. NAO is equipped with two cameras, four microphones, two loud speakers, nine tactile sensors, and eight pressure sensors (Figure 2).…”
Section: Humanoid Robot Naomentioning
confidence: 99%
“…The 25 degrees of freedom (Figure 1) provide NAO the capability to mimic almost all humanlike movement. Due to such features, NAO can be used in a multitude of the research environment, including assistive robotics, 42,47 healthcare robotics, [34][35][36] educations robotics, 48,49 etc. NAO is equipped with two cameras, four microphones, two loud speakers, nine tactile sensors, and eight pressure sensors (Figure 2).…”
Section: Humanoid Robot Naomentioning
confidence: 99%
“…In addition, robotics combines a variety of pedagogical approaches and theories, including project-based learning, real-world problems, constructivism, and collaboration (Morgan, 2019;Petraki & Herath, 2022;Zadok, 2020). Therefore, it is regarded as an effective approach in teaching since it makes theoretical concepts more tangible and accessible to students (Anwar et al, 2019;Bertel et al, 2019;Nugent et al, 2019). Many studies showed that students' performance in science, math, and/or STEM knowledge have improved by integrating robotics in teaching and learning (Baek et al, 2019;Chiang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…One of the best and easiest options to introduce AI-related technology (as well as science and technology in general) is through the use of robots or other intelligent agents. Humanoid robots are particularly suitable due to their complexity and human-likeness, but other robotic platforms are suitable as well [22][23][24][25]. The theory of embodied learning provides a theoretical foundation for such an approach [26], and social robots are appropriate tools for its realization [20,24].…”
Section: Introductionmentioning
confidence: 99%